If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -4) = 5(8 + -2x) Reorder the terms: 2(-4 + 3x) = 5(8 + -2x) (-4 * 2 + 3x * 2) = 5(8 + -2x) (-8 + 6x) = 5(8 + -2x) -8 + 6x = (8 * 5 + -2x * 5) -8 + 6x = (40 + -10x) Solving -8 + 6x = 40 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -8 + 6x + 10x = 40 + -10x + 10x Combine like terms: 6x + 10x = 16x -8 + 16x = 40 + -10x + 10x Combine like terms: -10x + 10x = 0 -8 + 16x = 40 + 0 -8 + 16x = 40 Add '8' to each side of the equation. -8 + 8 + 16x = 40 + 8 Combine like terms: -8 + 8 = 0 0 + 16x = 40 + 8 16x = 40 + 8 Combine like terms: 40 + 8 = 48 16x = 48 Divide each side by '16'. x = 3 Simplifying x = 3
| 7(2x-1)=3(15-4x) | | 6x^2+18=-21x | | -2v^2-5v-3=0 | | 1000=x+(x*.8)+(x*.3) | | 3.5q-1.4-5.9q=-3.4q-4.4 | | 1000=x+(x*.8)+(x*.5) | | -5y+4=-6y+5 | | 3x^2-14x=-18 | | 12x+6-3=11x-3 | | -10+3+6=-10 | | -4v^2-13v-3=0 | | -(8y+3)-(-7-4)=-1 | | 0.30(18)+0.05x=0.15(18+x) | | 8-4x+-6x=50 | | 4(2x-1)=2(3x+8) | | 4(3x+12)=2(2x+4) | | 1000=x+(x*.8) | | 3=2e^4x | | 9(x-36)=18 | | 2(x+4)=6(2x+3) | | 7(4x+6)+15= | | 4x-5=11-89 | | 6x+35=15x-55 | | 5a-3-4a+3=8 | | (4x^2+3x+5)-(6x^2-8)= | | 6a-2-5a+2=-2 | | X^2+17x=-72 | | -4a+3a-6=-4 | | 9x-19=5x+12 | | 6q-9=4q-19 | | c-5*4=-48 | | 4x+5=24 |